Magnifying Elements in Semigroups of Fixed Point Set Transformations Restricted by an Equivalence Relation - Thananya Kaewnoi; Ronnason Chinram; Montakarn Petapirak (Journal of Mathematics)
Let X be a nonempty set and ρ be an equivalence relation on X. For a nonempty subset S of X, we denote the semigroup of transformations restricted by an equivalence relation ρ fixing S pointwise by EFSX,ρ. In this paper, magnifying elements in EFSX,ρ will be investigated. Moreover, we will give the necessary and sufficient conditions for elements in EFSX,ρ to be right or left magnifying elements.